If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 2y + 5 + 4y = 0 Reorder the terms: 5 + y + 2y + 4y = 0 Combine like terms: y + 2y = 3y 5 + 3y + 4y = 0 Combine like terms: 3y + 4y = 7y 5 + 7y = 0 Solving 5 + 7y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 7y = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 7y = 0 + -5 7y = 0 + -5 Combine like terms: 0 + -5 = -5 7y = -5 Divide each side by '7'. y = -0.7142857143 Simplifying y = -0.7142857143
| 0=-6(x+5) | | 4a+2b+3=25 | | -t+2t-8t= | | 24x-216/x-6 | | 92-(6x-3)=4x | | 3x+10y=4.2 | | 5x^2-5x+4=4x | | 36-w^2= | | 4b-b+6= | | 2x^2+9=55 | | (72b)^1/2 | | 3/5x^(-2/5) | | 2(2y)-y=2y+y | | 8.9-33j=22j+23 | | 0=3x^4-2x^2+5x-4 | | 8d-7d= | | -2b+4c+3b= | | 14t^4+9t^3-42t^2= | | Y=5(12)+36 | | 9.2x+5.5514=158.234 | | -1.8+5=-10.8+4 | | -7w=3w+2 | | -8(1+5m)=-8-3m | | 4x=5y+133 | | 2w^2-11w+15= | | -51+b=-91 | | ((9m^2)/(3m))-((4m)/(3m))-((6)/(3m)) | | 3x+1y=145 | | 5+5x-3y+4= | | 3(4x+2)=8x+30 | | y=7.5(1.75) | | 17-5m=3(f-12) |